2021
DOI: 10.2196/21463
|View full text |Cite
|
Sign up to set email alerts
|

Factors Driving Citizen Engagement With Government TikTok Accounts During the COVID-19 Pandemic: Model Development and Analysis

Abstract: Background During the COVID-19 pandemic, growth in citizen engagement with social media platforms has enabled public health departments to accelerate and improve health information dissemination, developing transparency and trust between governments and citizens. In light of these benefits, it is imperative to learn the antecedents and underlying mechanisms for this to maintain and enhance engagement. Objective The aim of this study is to determine the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
2
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 42 publications
10
88
2
5
Order By: Relevance
“…Acknowledging that there are many ways to calculate engagement (Ballesteros-Herencia, 2020) and considering the specific affordances of each platform, we used the following formula proposed by Chen et al (2021) to calculate engagement for TikTok:…”
Section: Engagementmentioning
confidence: 99%
“…Acknowledging that there are many ways to calculate engagement (Ballesteros-Herencia, 2020) and considering the specific affordances of each platform, we used the following formula proposed by Chen et al (2021) to calculate engagement for TikTok:…”
Section: Engagementmentioning
confidence: 99%
“…According to the ELM, when individuals view COVID-19 fact-checks, released by official government social media accounts, they will refer to the corresponding central and peripheral cues to process the information, and then decide whether to share it or not. Based on the integration of existing research, this study advocates that peripheral cues include media richness [ 22 , 26 ], source credibility [ 27 , 28 ], social media capital [ 25 ], and social media strategy [ 29 ], while central cues include content theme and content importance [ 25 , 30 , 31 ]. To conclude, this study developed the theoretical framework shown in Figure 1 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study on TikTok also proved that videos with topics of the government's handling of the situation and guidelines information promoted citizens' sharing (Q. Chen et al, 2021 ).…”
Section: Theoretical Foundations and Hypothesismentioning
confidence: 90%
“…Though some recent work has explored the influencing mechanisms of engagement among citizens during crises (Q. Chen, Min, Zhang, Ma, & Evans, 2021 ; Q. Chen et al, 2020 ; Guo, Liu, Wu, & Zhang, 2021 ; Y.…”
Section: Introductionmentioning
confidence: 99%